Theoretical Research on the Processes of Cotton-Stage Linning and Lintering and Lintering (Eurasian Journal of Engineering and Technology, 2022)
The process of separating cotton fiber from seeds is very complicated. According to the current technological process, during the initial processing of cotton, after the ginning process, the surface of the seed is left with fibers capable of spinning. The presence of spinning fibers in the lint obtained during lintering and the fact that the total hairiness of the seeds is higher than the fruit limits the efficiency of the initial processing of cotton. In order to reduce the amount of short fibers in the fiber, increase the length of the staple mass of the fiber, reduce the amount of fibers in the fiber and the amount of fibers suitable for spinning and wool, as well as mechanical damage to the seed, the ginning process is different. density and the lintering process is carried out by softening the epidermal layer of the seed by additional moistening.